Relations between air pollution and vascular development in 5-year old children: a cross-sectional study in the Netherlands - Anna-Maria Ntarladima; Ilonca Vaartjes; Diederick E. Grobbee; Martin Dijst; Oliver Schmitz; Cuno Uiterwaal; Geertje Dalmeijer; Cornelis van der Ent; Gerard Hoek; Derek Karssenberg (BMC, 2019)
Abstract Background Air pollution has been shown to promote cardiovascular disease in adults. Possible mechanisms include air pollution induced changes in arterial wall function and structure. Atherosclerotic vascular disease is a lifelong process and childhood exposure may play a critical role. We investigated whether air pollution is related to arterial wall changes in 5-year old children. To this aim, we developed an air pollution exposure methodology including time-weighted activity patterns improving upon epidemiological studies which assess exposure only at residential addresses. Methods The study is part of an existing cohort study in which measurements of carotid artery intima-media thickness, carotid artery distensibility, elastic modulus, diastolic and systolic blood pressure have been obtained. Air pollution assessments were based on annual average concentration maps of Particulate Matter and Nitrogen Oxides at 5 m resolution derived from the European Study of Cohorts for Air Pollution Effects. We defined children's likely primary activities and for each activity we calculated the mean air pollution exposure within the assumed area visited by the child. The exposure was then weighted by the time spent performing each activity to retrieve personal air pollution exposure for each child. Time spent in these activities was based upon a Dutch mobility survey. To assess the relation between the vascular status and air pollution exposure we applied linear regressions in order to adjust for potential confounders. Results Carotid artery distensibility was consistently associated with the exposures among the 733 5-years olds. Regression analysis showed that for air pollution exposures carotid artery distensibility decreased per standard deviation. Specifically, for NO2, carotid artery distensibility decreased by − 1.53 mPa− 1 (95% CI: -2.84, − 0.21), for NOx by − 1.35 mPa− 1 (95% CI: -2.67, − 0.04), for PM2.5 by − 1.38 mPa− 1 (95% CI: -2.73, − 0.02), for PM10 by − 1.56 mPa− 1 (95% CI: -2.73, − 0.39), and for PM2.5absorbance by − 1.63 (95% CI: -2.30, − 0.18). No associations were observed for the rest outcomes. Conclusions The results of this study support the view that air pollution exposure may reduce arterial distensibility starting in young children. If the reduced distensibility persists, this may have clinical relevance later in life. The results of this study further stress the importance of reducing environmental pollutant exposures.